A comprehensive comparison of the fifth‐wave highly pathogenic and low‐pathogenic H7N9 avian influenza viruses reveals potential threat posed by both types of viruses in mammals. Issue 6 (17th July 2018) - He, Lihong; Liu, Dong; Hu, Jiao; Sun, Wenqiang; Gao, Ruyi; Shi, Lei; He, Dongchang; Li, Bo; Wang, Xiaoquan; Gu, Min; Hu, Shunlin; Liu, Xiaowen; et al.
Abstract: Before 2013, zoonotic influenza infections were dominated by H5N1 viruses in China. However, the emergence of the H7N9 viruses in early 2013 changed this dominance greatly, and more than 1, 600 laboratory‐confirmed human cases of H7N9 infections have been reported since then. To understand the underlying mechanism of the emergence of the fifth epidemic wave that shows an unexpected sharp increase, we systematically investigated the biological characteristics of the highly pathogenic (HP) and low‐pathogenic (LP) H7N9 AIVs during this period. We first systematically analysed the haemagglutination assay gene of all the isolates available from the website and found that the HP and LP viruses differed a little in the well‐established receptor binding sites and in other potentially important sites. Phylogenetic analysis showed that both the HP and LP viruses belong to the branch of the Yangtze River Delta, whereas they diverged to different small branches. To further compare the biological variations in the HP and LP viruses, we selected six HP and six LP strains for in‐depth analysis, including receptor binding characteristics, thermal stability, viral replication and virulence in mice. The three major findings of this study were as follows: (a) Other potential site/sites may affect the receptor binding property of the H7N9 viruses; (b) the HP viruses displayed a higher thermostability than did the LP viruses, quite consistent with the epidemiological data during the summer period; and (c) one‐third of the HP viruses were moderately pathogenic in mice, whereas all the LP viruses were nonpathogenic in this animal model. However, the LP viruses replicated more efficiently in the mouse lung and can spread to the extrarespiratory organs (spleen, kidney and brain). Taken together, our results suggest that both the HP and LP H7N9 viruses can pose a potential threat to public health, highlighting the importance of the continual surveillance of the H7N9 AIVs.